Combined non-alcoholic fatty liver disease and type 2 diabetes mellitus: sleeve gastrectomy or gastric bypass? ; a controlled matched pair study of 34 patients - Billeter, Adrian; Senft, Jonas; Gotthardt, Daniel; Knefeli, Philipp; Nickel, Felix; Schulte, Thilo; Fischer, Lars; Nawroth, Peter Paul; Büchler, Markus W.; Müller, Beat P. (Obesity surgery, 2016)
Although all bariatric procedures improve non-alcoholic fatty liver disease (NAFLD) in metabolically sick obese patients, it remains unclear whether different procedures achieve similar effects. Sleeve gastrectomy (SG) and Roux-Y-gastric bypass (RYGB) were compared for their effects on liver function tests (LFT) and glycemic control in a highly selected group of metabolically sick obese patients with both elevated alanine aminotransferase (ALT), a common marker for NAFLD and type 2 diabetes mellitus (T2DM).